IMPLEMENTASI KURIKULUM 2013 DAN PERSIAPAN PELAKSANAAN KURIKULUM MERDEKA PADA MATA PELAJARAN BIOLOGI DI SMA NEGERI 4 PANDEGLANG - Usman Usman; Iing Dwi Lestari; Hadiyati Adilla Ramdhani; Mutiara Runi; Nurkholis Nurkholis; Neneng Nuraliah; Annisa Khotimah; Atiti Wahdiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
The fact is that not everything is as expected by the demands of the 2013 curriculum, there will definitely be advantages and disadvantages that will occur in each curriculum. But every deficiency in implementing the curriculum is a challenge for Biology teachers at SMAN 4 Pandeglang to be able to find solutions to every problem. This study aims: to determine the extent to which the implementation of Biology learning using the 2013 curriculum at SMAN 4 Pandeglang. The method used is interviews with two teachers there, namely the Biology teacher and the teacher who is the driving force in the curriculum at the SMAN. As a result, the implementation of Biology learning using the 2013 curriculum at SMAN 4 Pandeglang can be said to be good. Biology teacher who has experienced teaching for about 36 years in the world of education. So, know how to solve an existing problem about the curriculum to be applied in the learning process. Then at SMAN 4 Pandeglang, they are planning to prepare the Independent Curriculum to be implemented next year.